2015
DOI: 10.1681/asn.2014010119
|View full text |Cite
|
Sign up to set email alerts
|

Persistent BK Viremia Does Not Increase Intermediate-Term Graft Loss but Is Associated with De Novo Donor-Specific Antibodies

Abstract: There are limited data regarding intermediate-term outcomes in patients with persistent BK viremia. Other viral infections have been implicated in the development of allosensitization through heterologous immunity, but the relationship between BK viremia and donor-specific antibodies (DSAs) is unexplored. In 2008, we initiated routine post-transplant BK viremia and DSA screening at our center; 785 kidney or kidney-pancreas transplant recipients were included in our study. Of these recipients, 132 (17%) recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
84
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 20 publications
12
84
2
4
Order By: Relevance
“…Urschel et al demonstrated that DSA occur more frequently in patients who are older at the time of HTx, a finding that is supported by our current analysis. Adult studies in solid organ transplant recipients also indicate that rejection episodes, HLA mismatch, pretransplant PRA > 10%, viral infections, and non‐compliance are associated with the development of DSA . Similar to these studies, our analysis suggests that elevated PRA pre‐HTx is associated with the development of DSA.…”
Section: Discussionsupporting
confidence: 79%
“…Urschel et al demonstrated that DSA occur more frequently in patients who are older at the time of HTx, a finding that is supported by our current analysis. Adult studies in solid organ transplant recipients also indicate that rejection episodes, HLA mismatch, pretransplant PRA > 10%, viral infections, and non‐compliance are associated with the development of DSA . Similar to these studies, our analysis suggests that elevated PRA pre‐HTx is associated with the development of DSA.…”
Section: Discussionsupporting
confidence: 79%
“…The incidence of graft loss overall was low, likely reflecting overall greater experience in managing BKPyVAN, as reported previously . The development of HLA antibodies has been reported after BKPyV infection in prior studies, but was not routinely performed in this cohort. Future studies should assess the relationship between early and late BKPyVAN and development of anti‐HLA antibodies.…”
Section: Discussionsupporting
confidence: 62%
“…Development of Donor specific antibodies leading to sequela of acute rejection seems to be a major consequence from reduction of immunosuppression for among patients with BKV infection with no available effective treatment options at this time . Thus, findings from our study on epidemiology of BKV genotypes may serve as a resource for development of vaccines against BKV in United States .…”
Section: Discussionmentioning
confidence: 91%